Fine Dining Restaurant Development As Culinary Destination Attraction In Bali To Achieve Michelin Stars Award - Firman Sinaga; Gede Yudiya Permana; Putu Eka Wirawan; I Gusti Made Suka Arnawa; Firli Lanovia Amir; Francisca Titing Koerniawaty (Faculty of teaching training and education, 2023)
The Michelin Guide had its start in the late 19th century, according to its website. The Michelin Guide in France to see how the quality of a restaurant should be. This institution only assesses the quality of food. Indonesia with its diverse culinary wealth and supported by many types of restaurants that serve world-class food, but to date none has won the Michelin Stars award. One of the fine dining restaurant in Bali, named BLANCO par Mandif Restaurant which through early observation have the potential to win this award associated with the Michelin Red Guide evaluation criterias. This study was a qualitative descriptive, using purposive sampling, in-depth interviews with the restaurant manager for data collection and the Miles and Huberman models for data analysis. The results showed that there are four main potential aspects of restaurant, namely of Core value, Chef personality, Menu, and Achievements, those represent fundamentals, identity and restaurant reputation, as well as awareness for the Michelin Company. The five aspects have chance to win the Michelin Stars award, while the rest are professional and credible assessments by the Michelin inspector. From this reserch hope the government cares about the Michelin Star Award